Constructing a Bias-Free Trade Governance Indicator: Revealing the Biases of Existing Survey Indicators - Shintaro Hamanaka; Aiken Tafgar; Ronald Ico (Asian Development Bank (ADB), 2015)
Governance is one of the key factors that shape the economic performance of an economy in terms of economic and trade growth. However, accurately measuring the quality of governance is not an easy task. Research typically uses governance indicators from surveys, which may have biases and inherent errors. In this paper, we attempt to construct an alternative governance indicator, which is free from perception and subjective biases. Our exercise is based on the inference that economies with good trade governance can compile high quality trade statistics; the latter being a close proxy for the former. This study comes up with a global ranking of the quality of (trade) governance. The paper also compares our bias-free indicator against existing survey governance indicators.
hdl:11540/5173
Keywords: F14; F15; 330; bias; corruption; governance; indicators; perception; survey; trade